THE ROLE OF ADVOCATES AS OFFICIUM NOBILE IN LAW ENFORCEMENT AND PROTECTORS CLIENT RIGHTS - Ervian, Ervan; Betharyana, Farel Putra; jaelani, Ahmad Fadhil (Jurnal Abdisci, 2025)
Abstract Background. The advocate profession has an important role in the Indonesian legal system as an officium nobile, with the task of enforcing the law, protecting the rights of clients, and ensuring justice. Aims. Advocates are on par with other law enforcers as stipulated in Law Number 18 of 2003 concerning Advocates. They are obliged to work professionally, independently, and with integrity, with a code of ethics as a moral and legal guideline to maintain public trust. Methods. In this study, the author uses a qualitative method with a descriptive approach to analyze the role of advocates in litigation and non-litigation as well as the challenges faced. Result. The results show that although advocates have a strategic role, there are still obstacles in the implementation of the code of ethics, such as conflicts of interest, economic pressure, and third-party intervention. Conclusion. Therefore, it is necessary to strengthen regulations, increase code of ethics supervision, and continue education so that the professionalism of advocates is maintained. Implementation.